Challenging policy barriers in sustainable urban design - Birkeland, Janis (Bulletin of Geography. Socio-economic Series, 2018)
In built environment design, codes set minimum health and safety requirements, policies set aspirational targets, and incentives such as green building rating schemes set design standards. These approaches have failed to provide universal wellbeing and environmental justice (i.e. intra-generational equity), or increases in the natural life-support system that exceed depletion rates (i.e. inter-generational equity). Governments that do not ensure all citizens can obtain basic needs, life quality and resource security fail to meet their basic responsibilities. Two recent documents, one representing sustainable urban policy and principles, the other representing urban biodiversity standards, are examined against the Positive Development Test (whether the development increases the public estate, ecological base and future public options). The discussion suggests that contemporary policies and incentive schemes, as presently conceived, cannot provide the basic physical preconditions for sustainability, let alone address socio-economic inequities. An alternative design-based approach is presented to address the issues the paper identified.